EXPLORATION OF BRAND POSITIONING AND DIFFERENTIATION DYNAMICSIN IMPROVING PRODUCT BRANDING - Harmiaty Bahar; Yussi Rahmawati; Muh. Husriadi (Adisam Publisher, 2025)
The market is growing competitive and digitalized demand companies to integrate positioning and differentiation strategies brand in a way effective use strengthen product branding. This research aims exploring the dynamics of positioning and differentiation integration brand in the context of improving product branding, with a focus on uniqueness feature product, coherence between brand position and attributes differentiation, as well as utilization of digital platforms for personalization experience consumers. The method used is qualitative research with data collection through interview deep to practitioners marketing and management brand. The results of the study show that unique product innovation and special features service is foundation capable differentiation​ strengthen brand position in a way authentic. Consistent coherence​ between promises in positioning and attributes applied differentiation​ build trust and loyalty consumers. In addition, personalization experience brand through digital platforms to improve proximity as well as relevance brands with consumers, encouraging stronger interactions and loyalty in the digital age. Implications practical from this research emphasizes importance strategic integration through coordination cross departments and the use of digital technology ethically to produce adaptive and sustainable branding. These findings contribute significant theoretical and practical implications in management development modern brands in the global market.